FROM PEER BULLYING TO CYBER BULLYING - Rizvance Masan, Sehida (International Scientific Journal Vision, 2021)
In this study, the concepts of "Peer Bullying" and "Cyber Bullying", which is in the form of a literature review, is discussed. In recent years, the number of studies on peer bullying are increased, which is the most common type of aggression among students at schools. This is because, the peer bullying have psychological, social and physical consequences over the children who bully as well as those who are exposed to being bullied. In addition, the development of the educational technologies, the use of the internet and mobile devices became a part of school of their life, have also led to an increase in the number of cyberbullying cases. Today, it is seen that the peer bullying among students is becoming more intense in virtual environments, such as the internet and mobile phones. Identifying the overlapping between bullying and cyberbullying or revealing and examining the similarities and differences of these two phenomena is one of the important research topics in this field. In this study, it is aimed to contribute to the literature by reviewing the definitions of peer bullying and cyberbullying, which are very common and important problems in most cultures, the similarities and differences between both types of bullying, and the studies conducted around the world on this subject.